Meta-Analysis of the Effect of Physical Exercise on Decrease Blood Sugar Levels in Type-2 Diabetes Mellitus Patients - Tri Nyantosani Widyawardani; Diyanti Safitri (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Diabetes Mellitus is a major health problem worldwide, the number of sufferers is expected to increase rapidly every year. Handling to achieve controlled sugar levels requires the integration of drugs, diet and physical exercise. This study aimed to analyze the effect of physical exercise on reducing blood sugar levels in patients with type 2 diabetes mellitus.Subjects and Method: This study uses the PRISMA flowchart to perform the meta-analysis. The article review process took place between 2017 and 2022 with PICO as follows, Population: type-2 diabetes mellitus sufferers. Intervention: physical exercise. Comparison: not doing physical exercise. Outcome: decrease in blood sugar levels, articles collected using databases such as PubMed, Google Scholar, and Science Direct. The articles obtained will be filtered using the stages according to the PRISMA flow diagram. The analysis was carried out using RevMan 5.3.Results: A total of 9 articles reviewed in the meta-analysis showed that physical exercise reduced blood sugar levels in type 2 diabetes mellitus patients with statistical significance (SMD= -0.44; 95% CI= -0.84 to -0.05; p= 0.030).Conclusion: Physical exercise lowers blood sugar levels in people with type 2 diabetes mellitus..Keywords: physical exercise, diabetes mellitus type 2, decrease in blood sugar levels.Correspondence:Tri Nyantosani Widyawardani. District Health Office of Klaten, Central Java. Jl. Pemuda Nomor 313, Mlinjon, Tonggalan, Central Klaten, Central Java, 5741. Email: nyantosani@gmail.com. Mobile: +62811284836.Journal of Health Promotion and Behavior (2022), 07(02): 119-131DOI: https://doi.org/10.26911/thejhpb.2021.07.02.04